Differences in outcomes of patients with in-hospital versus out-of-hospital ST-elevation myocardial infarction: a registry analysis - Sarah Zaman; Angela L Brennan; Jeffrey Lefkovits; Julia Stehli; Diem T Dinh; Stephen J Duffy; Misha Dagan; Ron Dick; Stephanie Oxley (BMJ Open, 2022)
Objectives Patients with ST-elevation myocardial infarction (STEMI) that occur while already in hospital (‘in-hospital STEMI’) face high mortality. However, data about this patient population are scarce. We sought to investigate differences in reperfusion and outcomes of in-hospital versus out-of-hospital STEMI.Design, Setting and Participants Consecutive patients with STEMI all treated with percutaneous coronary intervention (PCI) across 30 centres were prospectively recruited into the Victorian Cardiac Outcomes Registry (2013–2018).Primary and secondary outcomes Patients with in-hospital STEMI were compared with patients with out-of-hospital STEMI with a primary endpoint of 30-day major adverse cardiovascular events (MACE). Secondary endpoints included ischaemic times, all-cause mortality and major bleeding.Results Of 7493 patients with PCI-treated STEMI, 494 (6.6%) occurred in-hospital. Patients with in-hospital STEMI were older (67.1 vs 62.4 years, p<0.001), more often women (32% vs 19.9%, p<0.001), with more comorbidities. Patients with in-hospital STEMI had higher 30-day MACE (20.4% vs 9.8%, p<0.001), mortality (12.1% vs 6.9%, p<0.001) and major bleeding (4.9% vs 2.3%, p<0.001), than patients with out-of-hospital STEMI. According to guideline criteria, patients with in-hospital STEMI achieved symptom-to-device times of ≤70 min and ≤90 min in 29% and 47%, respectively. Patients with out-of-hospital STEMI achieved door-to-device times of ≤90 min in 71%. Occurrence of STEMI while in hospital independently predicted higher MACE (adjusted OR 1.77, 95% CI 1.33 to 2.36, p<0.001) and 12-month mortality (adjusted OR 1.49, 95% CI 1.08 to 2.07, p<0.001).Conclusions Patients with in-hospital STEMI experience delays to reperfusion with significantly higher MACE and mortality, compared with patients with out-of-hospital STEMI, after adjustment for confounders. Focused strategies are needed to improve recognition and outcomes in this high-risk and understudied population.